The Many Faces of Acute Idiopathic Blind Spot Enlargement - Ho, Amiee; Goodwin, Denise (Canadian Journal of Optometry, 2021)
This is a literature review and retrospective case series of acute idiopathic blind spot enlargement of 2 Caucasian females and 1 Hispanic male. Hallmark findings include unilateral photopsia, an enlarged blind spot, loss of the ellipsoid and interdigitation zones on OCT, and an abnormal multifocal electroretinography. This condition is an outer retinal disease that shares common traits with the AZOOR complex, which can confound the diagnosis. Autofluorescent imaging may aid in differentiating the conditions. Disseminating more case reports detailing different presentations of this rare outer retinal disorder help advance the clinical understanding of these conditions.